Effectiveness and Safety of Nebulized Magnesium as Last Line Treatment in Adults with Acute Asthma Attack: A Systematic Review and Meta-Analysis - Danny Darmawan; Iris Rengganis; Cleopas Martin Rumende; Hamzah Shatri; Soekamto Koesnoe; Yogi Umbarawan; Rudi Putranto; Sally Aman Nasution (Interna Publishing, 2024)
Background: Asthma is a disease characterized by chronic airway inflammation, however one-third of asthmatic cases did not respond adequately. Inhaled magnesium has been proposed as a treatment for unresponsive asthma cases. However, its role remains controversial. This review evaluates the effectiveness and safety of nebulized magnesium compared to standard therapy (Beta Agonist, Anticholinergic, Corticosteroid) in adults with acute asthma attacks. Methods: The protocol has been registered in PROSPERO. A literature search was conducted through PubMed/MEDLINE, Cochrane, ProQuest, and Google Scholar, and using the keywords "inhaled magnesium" and "asthma". Manual searches were carried out through data portals. Journal articles included are randomized controlled trials. The assessment risk of bias was performed using Version 2 of the Cochrane risk-of-bias tool for randomized trials. Results: There are five articles included in this review. There is no significant difference in readmission rate and oxygen saturation in the magnesium group compared to control (RR 1; 95% CI 0.92 to 1,08; p= 0,96 and MD 1,82; 95% CI -0.89 to 4.53; p= 0.19, respectively). There is a significant reduction of respiratory rate and clinical severity in magnesium (MD -1,72; 95% CI -3,1 to 0.35; p= 0.01, RR 0.29; 95% CI 0.17 to 0.69; p <0.001, respectively). There was a higher risk of side effects in the magnesium group (HR 1.56; 95%CI 1.05 to 2.32; p= 0.03). However, the side effects are relatively mild such as hypotension and nausea. Conclusion: Inhaled magnesium improves the outcome of asthmatic patients, especially in lung function, clinical severity, and respiratory rate. Moreover, inhaled magnesium is safe to be given.